2005
DOI: 10.1200/jco.2005.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Administration of High-Dose Rituximab Before and After Autologous Stem-Cell Transplantation for Relapsed Aggressive B-Cell Non-Hodgkin’s Lymphomas

Abstract: The results of this study suggest that using HD-R and autologous SCT is a feasible and promising treatment for patients with B-cell aggressive NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 28 publications
5
66
3
Order By: Relevance
“…54,55 Thus, our study further strengthens the evidence for the benefit of adding rituximab to intensive programs with autograft for DLB-CL patients, exploiting not only its antitumor activity, but also its in vivo purging effect on PBSC harvests. [10][11][12][13]56,57 In conclusion, the efficacy of combining early hd-chemotherapy, multiple PBPC support and rituximab in high-risk DLB-CL is shown in this prospective multicenter study, confirming the recent promising observations with early dose intensity and autograft in poor prognosis aggressive lymphoma. 5,7,8 Thus, in spite of a number of novel treatment approaches that are under development and are expected to improve our lymphoma management strategies, intensified treatments with autograft should still be considered as effective therapeutic weapons, worthy of being evaluated in comparison with other intensified chemoimmunotherapy schedules not requiring autologous progenitor cell support.…”
Section: Tablesupporting
confidence: 76%
“…54,55 Thus, our study further strengthens the evidence for the benefit of adding rituximab to intensive programs with autograft for DLB-CL patients, exploiting not only its antitumor activity, but also its in vivo purging effect on PBSC harvests. [10][11][12][13]56,57 In conclusion, the efficacy of combining early hd-chemotherapy, multiple PBPC support and rituximab in high-risk DLB-CL is shown in this prospective multicenter study, confirming the recent promising observations with early dose intensity and autograft in poor prognosis aggressive lymphoma. 5,7,8 Thus, in spite of a number of novel treatment approaches that are under development and are expected to improve our lymphoma management strategies, intensified treatments with autograft should still be considered as effective therapeutic weapons, worthy of being evaluated in comparison with other intensified chemoimmunotherapy schedules not requiring autologous progenitor cell support.…”
Section: Tablesupporting
confidence: 76%
“…A recent follow-up of the expanded study reported that the projected 3-year OS and relapsefree survival to be 91 and 84%, respectively. Khouri et al 25 and the MD Anderson Cancer Center used premobilization rituximab followed by BEAM in combination with highdose rituximab (1000 mg/m 2 ) after transplant. Sixty-seven aggressive NHL patients treated with this approach successfully underwent stem cell harvest and transplantation.…”
Section: Original Approachmentioning
confidence: 99%
“…In a second trial, high-dose rituximab, 1000 mg/m 2 rather than standard-dose 375 mg/m 2 , was administered during stem cell mobilization, BEAM (carmustine, etoposide, cytarabine, melphalan) chemotherapy, and on days 1 and 8 after HSCT in 67 patients. 21 At a median follow-up of 20 months, estimated 2-year disease-free and overall survival (OS) were 67% and 80%, respectively (P = 0.002), significantly better than those of a historical control group receiving the same preparative regimen without rituximab 43% and 53%, respectively (P = 0.004).…”
Section: Dlbcl Treatmentmentioning
confidence: 98%